Exchange rate misalignment: The case of the Chinese Renminbi - Yin-Wong Cheung (Center for Economic Studies and ifo Institute (CESifo), 2012)
Assessing exchange rate misalignment is not an easy task. With reference to the debate on the value of China's currency, the renminbi (RMB), this article highlights a few challenges in properly assessing the extent of currency misalignment. The results derived from the fundamental equilibrium exchange rate (FEER) approach and the Penn effect regression are used to illustrate the sensitivity of misalignment estimate to assumptions of the key parameters in a given model, sampling uncertainty, serial correlation adjustment, and data revision. It is shown that both the sign and the magnitude of a misalignment estimate could be dramatically affected by these factors.
Keywords: F31; F41; 330; FEER; Penn effect; sampling uncertainty; serial correlation; data revision